Species richness and composition of odonata in four swamp forests of Terengganu, peninsular Malaysia - Muhammad Adam-Ibrahim,; Amirrudin B. Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Odonata is an insect order that includes dragonflies and damselflies. These cunning and swift-flying insects are known to be habitat specialists and are often sensitive to environmental changes. Studies on Odonata diversity in tropical areas are still limited, especially in swampy areas that are often subject to anthropogenic disturbances. A study was conducted in four different swampy areas in Terengganu, Malaysia, to assess the Odonata diversity in these areas. Four sampling days were spent at each study site between February and June 2023. A total of 1,843 individuals were collected, representing 63 species from ten families. Ten of these were new records for Terengganu. The family Libellulidae was the most well-represented family, with Neurothemis fluctuans being the most abundant species. Some notable findings from the study include the occurrence of the uncommon Heliaeschna simplicia, Pornothemis cf. serrata, Risiophlebia dohrni, and Teinobasis ruficollis. Species richness was highest in Tasik Bungkus (36 species), followed by Jambu Bongkok, Sungai Ular, and Bandar Kuala Nerus. These findings provide new insights into the Odonata diversity of swampy areas in Terengganu. The discovery of stenotopic species (species restricted to specific habitats) is particularly important, as these species are often vulnerable to changes in environmental quality. The study also highlights the need for further research on Odonata diversity in tropical areas, especially in swampy areas that are under threat of urbanisation